Dampak Deposito, Kredit, dan BI Rate terhadap Pertumbuhan Ekonomi di Indonesia - lia dahliyati; Maizul Rahmizal (Universitas Negeri Padang, 2026)
This study is based on the importance of economic growth as a key indicator of economic performance reflected in Gross Domestic Product (GDP). The role of the banking sector as a financial intermediary and monetary policy through the BI Rate influences the dynamics of Indonesia’s economic growth. Empirical observations show that deposits, credit, and the BI Rate did not always move in line with GDP during the 2010–2024 period, indicating the need for an empirical analysis of their relationships. The aim of this study is to examine the effect of deposits, credit, and the BI Rate on Indonesia’s economic growth in both the short run and the long run. This research employs a quantitative approach with an explanatory design using quarterly time series data from 2010Q1 to 2024Q4. The analysis method applies the Autoregressive Distributed Lag (ARDL) model to capture both short-run and long-run relationships and the Error Correction Model (ECM) to assess the adjustment process toward equilibrium. The results show that credit has a positive and significant effect on economic growth in both the short run and long run. Deposits do not have a significant effect on economic growth. The BI Rate also does not significantly affect economic growth in either period. Credit emerges as the most influential variable in driving economic activity through the channeling of funds to the real sector.